Enhancing innovation capacity as a key factor of innovative breakthrough - Utegenova , Zh.S. (BUKETOV BUSINESS REVIEW, 2017)
Prevailing recent global economic trends prove the fact that all the advanced countries of the world are on an innovative path of development that allows them to maintain their economic and political domination. Moreover, among the world's leaders are joining more and more new countries from developing, have achieved leading economic growth rates due to the high innovativeness of their national economies. In this regard, the formation of a new, improved model of management of innovative development of the Republic of Kazakhstan can most effectively and quickly ensure the stable development of the economy faster pace. The changing context for innovative development has highlighted a strong need to understand and adopt innovation systems thinking. Science, technology and innovation policy has equated countries development to innovative development. The main objective of this paper was to examine the role of innovation capacity in a whole innovational sector. Also the paper is to review and to describe, innovation system and state innovation policy so it deals with the problems of innovation activity, increase innovation capacity and presents proposals to improve the whole country's innovation development.